Hematological Test: Predicting Incidence Dengue Shock Syndrome - Yamin, Imam Syahputra; Wahyono, Tri Yunis Miko (Universitas Islam Negeri Mataram, 2021)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the Dengue virus. DHF cases in Mataram City from 2016 to 2020 tend to increase where most of the DHF patients are treated at the Mataram City Hospital. Death due to DHF infection mostly occurred in patients with Dengue Shock Syndrome (DSS) and mortality from DSS was reported to be 50 times higher than in DHF patients without DSS. Prompt diagnosis and appropriate treatment are important determinants for the prevention and control of dengue cases, so knowing the predictors of risk factors can prevent/reduce deaths from dengue virus. This study used a case-control design. Cases were DHF patients diagnosed with DSS by the treating doctor, while the controls were DHF patients diagnosed not DSS by the treating doctor. The research data was obtained from the results of laboratory tests stored in the medical records of patients treated at the Mataram City Hospital from January 2016 to December 2020. The design of the analysis was aimed at obtaining the odds ratio (OR) value followed by multivariate analysis to determine the risk factors that could detect DSS earlier. The variables that were statistically significant in the prediction of the final model were the increase in hematocrit value > baseline with OR= 17.1 (95% CI: 4.033-72.600), a decrease in platelet value < 100.000/µL with OR = 6 (95% CI). : 2,306-15,699), and decreased leukocyte value < baseline with OR= 5.1 (95% CI: 2,209-11,838). While the most dominant variable is the increase in hematocrit value > baseline with OR = 17.1 (95% CI: 4.033-72.600) and p value = 0.000.